Disparities in acute decompensated heart failure. (May 2021) - Miller, Tamari; Carter, Spencer V.; Smith, Bryan A.
Abstract : Purpose of review: The aim of this review is to discuss racial and sex disparities in the management and outcomes of patients with acute decompensated heart failure (ADHF). Recent findings: Race and sex have a significant impact on in-hospital admissions and overall outcomes in patients with decompensated heart failure and cardiogenic shock. Black patients not only have a higher incidence of heart failure than other racial groups, but also higher admissions for ADHF and worse overall survival, while women receive less interventions for cardiogenic shock complicating acute myocardial infarction. Moreover, White patients are more likely than Black patients to be cared for by a cardiologist than a noncardiologist in the ICU, which has been linked to overall improved survival. In addition, recent data outline inherent racial and sex bias in the evaluation process for advanced heart failure therapies indicating that Black race negatively impacts referral for transplant, women are judged more harshly on their appearance, and that Black women are perceived to have less social support than others. This implicit bias in the evaluation process may impact appropriate timing of referral for advanced heart failure therapies. Summary: Though significant racial and sex disparities exist in the management and treatment of patients with decompensated heart failure, these disparities are minimized when therapies are properly utilized and patients are treated according to guidelines.